On the hydro-dispersive equivalence between multi-layered mineral barriers - Guyonnet, Dominique; Perrochet, Pierre; Come, Bernard; Seguin, J J; Parriaux, Aurèle (My University, 2001)
In the context of municipal solid waste and hazardous waste disposal, the notion of "equivalence" between different barrier designs appears in regulatory documents from several industrialized countries. While in the past, equivalence has been thought of mainly in terms of contaminant travel times, in recent years it has been defined more in terms of the magnitude of a disposal site's potential impact on groundwater resources. This paper presents some original analytical solutions to the problem of contaminant migration through a multi-layered mineral barrier. The solutions account for the two major mechanisms of subsurface contaminant migration, namely, advection and diffusion-dispersion. An example application using the proposed solutions and a numerical model illustrates how one multi-layered mineral barrier can be considered superior to another from a strictly hydro-dispersive viewpoint. The influence of partial saturation of the mineral barrier is investigated using a numerical solution to the Richards equation for unsaturated flow. It is emphasized that conclusions relative to the superiority of one multi-layered barrier, with respect to another, should not only consider hydro-dispersive aspects, but also other processes such as the mechanical and chemical evolutions of the different barrier components. Although such phenomena are poorly addressed by existing models, failure to take them into account, at least in a qualitative fashion, may lead to unconservative conclusions with respect to barrier equivalence. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: contaminant transport; barrier equivalence; waste disposal; modelling; GEOSYNTHETIC CLAY LINERS; HYDRAULIC CONDUCTIVITY; DISPOSAL SITES; GROUNDWATER; TRANSPORT; FLOW